Super Stretchable, Self‐Healing, Adhesive Ionic Conductive Hydrogels Based on Tailor‐Made Ionic Liquid for High‐Performance Strain Sensors - Yao, Xue; Zhang, Sufeng; Qian, Liwei; Wei, Ning; Nica, Valentin; Coseri, Sergiu; Han, Fei (Advanced functional materials, 2022)
Ionic conductive hydrogels (ICHs) integrate the conductive performance and soft nature of tissue‐like materials to imitate the features of human skin with mechanical and sensory traits; thus, they are considered promising substitutes for conventional rigid metallic conductors when fabricating human‐motion sensors. However, the simultaneous incorporation of excellent stretchability, toughness, ionic conductivity, self‐healing, and adhesion via a simple method remains a grand challenge. Herein, a novel ICH platform is proposed by designing a phenylboronic acid‐ionic liquid (PBA‐IL) with multiple roles that simultaneously realize the highly mechanical, electrical, and versatile properties. This elaborately designed semi‐interpenetrating network ICH is fabricated via a facile one‐step approach by introducing cellulose nanofibrils (CNFs) into the PBA‐IL/acrylamide cross‐linked network. Ingeniously, the dynamic boronic ester bonds and physical interactions (hydrogen bonds and electrostatic interactions) of the cross‐linked network endow these hydrogels with remarkable stretchability (1810 ± 38%), toughness (2.65 ± 0.03 MJ m−3), self‐healing property (92 ± 2% efficiency), adhesiveness, and transparency. Moreover, the construction of this material shows that CNFs can synergistically enhance mechanical performance and conductivity. The wide working strain range (≈1000%) and high sensitivity (GF = 8.36) make this ICH a promising candidate for constructing the next generation of gel‐based strain sensor platforms. A novel semi‐interpenetrating network polyacrylamide/phenylboronic acid‐ionic liquid/cellulose nanofibril hydrogel (PAM/PBA‐IL/CNF) is proposed based on a “tailor‐made” PBA‐IL with multiple roles. Benefiting from the ingenious structural design, the PAM/PBA‐IL/CNF simultaneously displays the excellent comprehensive merits: (i) a fine trade‐off between electrical and mechanical performance, (ii) high strain sensitivity, favorable adhesion, self‐healing property, transparency and water retention.